Potentially disruptive life events: what are the immediate impacts on chronic disease management? A case-crossover analysis. Issue 8 (4th August 2016) - Lauffenburger, Julie C; Gagne, Joshua J; Song, Zirui; Brill, Gregory; Choudhry, Niteesh K
Abstract : Objective: To explore the association between unexpected potentially disruptive life events in a patient or family member that may challenge an individual's ability to take medications as prescribed and the discontinuation of evidence-based medications for common, chronic conditions. Understanding the relationship between medication adherence and life stressors, especially those that can be identified using administrative data, may help identify patients at risk of non-adherence. Design: Observational self-controlled case-crossover design. Setting: Individuals in a nationally representative US commercial health insurance database. Participants: Adult individuals who initiated an oral hypoglycaemic, antihypertensive and/or statin and subsequently stopped the medication for ≥90 days. Main outcome measure: Potentially disruptive life events among patients and their family members measured in the 30 days just before the medication was discontinued ('hazard period') compared with the 30 days before this period ('control period'). These events included personal injury, hospitalisation, emergency room visits, changes in insurance coverage, acute stress or acute anxiety. Results: Among the 326 519 patients meeting study criteria who discontinued their chronic disease medications, 88 896 (27.2%) experienced at least one potentially disruptive life event. Newly experiencing an injury (OR: 1.26, 95% CI 1.12 to 1.42), an emergency room visit (OR: 1.19, 95% CI 1.13 to 1.26) and acute stress (OR: 1.19, 95% CI 1.08 to 1.31) were associated with discontinuation. Life events among patients' family members did not appear to be associated with medication discontinuation or occurred less frequently just prior to discontinuation. Conclusions: Potentially disruptive life events among individuals identified using routinely collected claims data are associated with discontinuation of chronic disease medications. Awareness of these events may help providers or payers identify patients at risk of non-adherence to maximise patient outcomes.